Impact of Temporality and Identifiability in Online Deliberations on Discussion Quality: An Experimental Study - Strandberg, Kim; Berg, Janne (Javnost-The Public, 2015)
There is a perception that citizen deliberation brings about higher-quality discussions than discussions where deliberative norms are not used. Often, deliberations are realised in mini-publics in which certain contextual features ensure, a priori, that the discussions are likely to be of a high quality. However, few studies have as yet explored the boundaries of deliberation; that is, contemplated what happens to discussion quality if the ideal-speech situation is strayed away from. To address this point, this article reports on an online experiment in which the discursive setting of citizen deliberations is manipulated. The experiment (n = 50 participants) was carried out online in Finland in November 2013 in order to test the impact on discussion quality related to two factors: the temporality (asynchronous or synchronous discussions) and identifiability of participants (known or anonymous) in an online deliberation. The findings clearly indicate that asynchronous discussions have the most positive influence on discussion quality. Moreover, the identifiability factor only had a small weak influence on discussion quality, and there was only one weak interaction effect between the two factors.